Wirtschaftsstufe und Pflanzendecke - Geobotanische Differenzierung von Landschaften im Mittelmeerraum und in Chile - Deil, Ulrich; Scherer, Michael (ERDKUNDE, 1996)
In regions with identical physical and biotic conditions, but which are subjected to the impact of different societies and ethnic groups, the anthropogenetic transformation of the vegetation cover can be investigated. For this ethnogeobotanical approach we have chosen two areas: first, the peninsulas on both sides of the Strait of Gibraltar with an agro-industrial management by great landowners in Spain and a pre-industrial, smallholder farming in Morocco. Secondly, the Central Valley of Southern Chile near Temuco, where cash-crop farming by European colonists and self-sustaining farming by the Mapuche Indians are practised side by side. The studies are carried out at three levels (plant community, vegetation complex and vegetation region). We present here the results from level 3. The actual vegetation regions are documented in vegetation and land use maps from the Gibraltar and the Temuco areas and by a comparative table oft the plant communities in the coastal regions near Almarchal (Spain) and the Tangier Hinterland (Morocco). Characteristic vegetation units for the Spanish and the Moroccan side respectively can be established. Anthropogenetic differences are more important than natural ones, but they are mostly linked to economic effects, not to ethnogeobotanical influences in a stricter sense. Finally, some aspects of cultural ecology and recent landscape evolution are discussed.